Evaluating the WHO leadership in emergencies training programme: participants' perspective - Tabche, Celine; Atwan, Zeenah; Al-Mutawakel, Samar; Andriamiseza, Noémie; Popovich, Maria; Augustyniak, Ela; Black, Andrew; Utunen, Heini; Rawaf, Salman (Frontiers in Disaster and Emergency Medicine, 2025)
BackgroundThe Leadership in Emergencies (LIE) training programme, developed by WHO's Health Emergencies (WHE) Learning and Capacity Development Unit (LCD) and Eastern Mediterranean Region (EMR) Health Emergencies Department, aims to enhance emergency management and responders' technical and operational skills. WHO implemented a four-phase leadership programme to address leadership gaps in emergency response. This study evaluates its effectiveness using participant surveys and in-depth interviews.MethodsA total of 207 participants completed the survey, with 10 providing qualitative insights through interviews. The WHO Research Ethics Review Committee approved the study. It assessed the application of non-technical skills, field-level public health expertise, project management in humanitarian settings, and leadership competencies.ResultsParticipants frequently applied communication (35.7%), teamwork (36.7%), problem-solving (37.2%), and emotional intelligence (37.7%) skills. Field-level public health skills were frequently applied by 42.5%, and project management skills by 86.5%. Many reported career advancements, improved leadership, networking, stress management, and strategic thinking. The training was relevant, particularly simulation exercises, but challenges included balancing training with professional duties. Participants highlighted the need for structured follow-up. Future training should incorporate ongoing support mechanisms and emphasize simulation exercises and stakeholder engagement.ConclusionThe findings highlight the necessity of ongoing evaluations, practical simulations, and continuous enhancement of training programmes.